Entrepreneurial Literacy and Digital Literacy: A Key to Successful Business Sustainability of Clothing Merchants in the Modern Era - Marnoto Marnoto; Andi Syahriana Asdar; Rachmawati Novaria; Alisyahbana Alisyahbana (Department of Business and Entrepreneurship, Faculty of Economics and Business, Universitas Negeri Makassar, 2024)
This research aims to determine the sustainability of the clothing merchant business in the Modern Era by focusing on three variables, namely entrepreneurial literacy, digital literacy and business sustainability. This research uses a qualitative method with a phenomonological approach, and uses data collection techniques by interviews, direct observation of the research object. Then this research used 3 informants as research subjects, where these informants were the 3 most famous traders and had the largest business turnover in Makassar City. The Interaction Analysis Model uses concepts from Miles and Huberman. The research results show that the entrepreneurial literacy and digital literacy of clothing traders in this modern era can be categorized as good enough to support the development of these clothing traders. This is because traders have an understanding of the business they are establishing, never neglect in carrying out their obligations and things that could disrupt the continuity of their business. Meanwhile, business continuity shows that the clothing merchant business can be categorized as quite good, because it can develop and run well in line with increasingly modern developments.